If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = m + -63 Reorder the terms: 4 = -63 + m Solving 4 = -63 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 4 + -1m = -63 + m + -1m Combine like terms: m + -1m = 0 4 + -1m = -63 + 0 4 + -1m = -63 Add '-4' to each side of the equation. 4 + -4 + -1m = -63 + -4 Combine like terms: 4 + -4 = 0 0 + -1m = -63 + -4 -1m = -63 + -4 Combine like terms: -63 + -4 = -67 -1m = -67 Divide each side by '-1'. m = 67 Simplifying m = 67
| 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 | | 8g-7=-39 | | 3y+2f-f+1-3y+7=32 | | 2k+5=3 | | -5n+3=-4n-4 | | -6=-6w+4(w+3) | | 4b^2-169y^2= | | 9x+3x=10101010101001101 | | c+bc-11c-4=13c+4-2 | | 2k+10=k+15 |